Peran Kompetensi dan Etika Auditor Internal sebagai Determinan Kualitas Audit Persediaan - Kurniati Kurniati; Andi Anugrah Tegar Pratama; Masyhuri Masyhuri (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study aims to analyze the role of internal auditor competence and ethics as determinants of inventory audit quality, considering that inventory is an asset component that is prone to misstatement and manipulation, thus requiring professional and ethical audit supervision. The study uses the Systematic Literature Review (SLR) method by examining various academic literature, professional standards, and empirical research results in the last ten years that are relevant to auditor competence, professional ethics, and inventory audit quality. The results show that internal auditor competence, including mastery of audit procedures, understanding of the inventory cycle, and analytical skills, consistently has a significant effect on audit quality. In addition, auditor ethics and integrity have been proven to be moral factors that maintain the objectivity, independence, and courage of auditors in revealing findings related to inventory irregularities. The discussion shows that inventory audit quality is the result of a combination of auditor technical competence, professional ethics, and internal control structure support. In conclusion, a quality inventory audit is achieved when organizations simultaneously strengthen the competence and ethics of internal auditors.